Associations of migrant and refugee status with physical comorbidity and mortality among young adults with incident non-affective psychotic disorders - Alexis E. Cullen; Christopher J. de Montgomery; Emma Pettersson; Aemal Akhtar; Marie Norredam; Heidi Taipale; Ellenor Mittendorfer-Rutz (BMC Public Health)
Abstract Background Whilst a ‘healthy migrant effect’ has been reported for some migrant groups, it is unclear whether this generalises to individuals with non-affective psychotic disorders (NAPDs), a population characterised by increased risk of physical morbidity and mortality. We aimed to compare the risk of developing physical conditions, all-cause mortality, and suicide among Swedish-born, non-refugee migrant, and refugee individuals with incident NAPDs. Method In this register-based cohort study, nationwide registers were used to identify individuals aged 18–35 years who received their first diagnosis of NAPD in inpatient/specialist outpatient care between 1 January 2006 and 31 December 2013. Individuals were followed from the date of cohort entry until 31 December 2018 or death/emigration. Cox proportional hazards models (yielding hazard ratios, HRs and 95% confidence intervals, CI), incorporating inverse-probability weights to account for covariate differences across population groups, were used to compare the risk of specific physical disorders, all-cause mortality, and suicide in refugees and non-refugee migrants to their Swedish-born peers. Results We identified 7,733 individuals (median age 26, IQR 22–30 years; 63.6% male) with incident NAPDs. Compared to their Swedish-born peers, the risk of developing type 2 diabetes was significantly increased among refugees (HR = 2.48, 95% CI = 1.56–3.95) and non-refugee migrants (HR = 1.66, 95% CI = 1.01–2.71) with NAPDs, refugees were also at higher risk of infectious diseases (HR = 1.30, 95% CI = 1.09–1.55). No significant differences in cardiovascular and respiratory diseases were observed. In contrast, refugees with NAPDs had lower risk of all-cause mortality (HR = 0.59, 95% CI = 0.39 − 0.91) and deaths due to suicide (HR = 0.57, 95% CI = 0.34 − 0.96) compared to Swedish-born individuals with NAPDs. Conclusion Among those with NAPDs, migrants (particularly refugees) are at greater risk of developing diabetes and infectious diseases. Given the global increase in refugee populations, our findings have important implications for healthcare providers and suggest that these vulnerable individuals may require closer monitoring of physical health.